2017
DOI: 10.1038/srep41775
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutritional and ambient oxygen condition on biofilm formation in Mycobacterium avium subsp. hominissuis via altered glycolipid expression

Abstract: Mycobacterium avium subsp. hominissuis (MAH) is the major causative agent of nontuberculous mycobacteriosis, the representative case of environment-related infectious diseases the incidence of which is increasing in industrialized countries. MAH is found in biofilm in drinking water distribution system and residential environments. We investigated the effect of gaseous and nutritional conditions, and the role of glycopeptidolipids (GPLs) on biofilm-like pellicle formation in MAH. Pellicle formation was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…The common environment under these conditions is hypoxia as suggested by low oxygen concentration in natural water, tuberculous granuloma and inside biofilms in biofilm-forming bacteria 18,19,21 . First, we confirmed that, similar to pellicle formation in MAH as we demonstrated previously 16 , M. intracellulare ATCC13950 formed a pellicle under an atmosphere of 5% oxygen (Fig. S1).…”
Section: Comparison Of Gene Essentiality Between M Intracellulare Ansupporting
confidence: 89%
See 2 more Smart Citations
“…The common environment under these conditions is hypoxia as suggested by low oxygen concentration in natural water, tuberculous granuloma and inside biofilms in biofilm-forming bacteria 18,19,21 . First, we confirmed that, similar to pellicle formation in MAH as we demonstrated previously 16 , M. intracellulare ATCC13950 formed a pellicle under an atmosphere of 5% oxygen (Fig. S1).…”
Section: Comparison Of Gene Essentiality Between M Intracellulare Ansupporting
confidence: 89%
“…1). The protocol of planktonic and pellicle bacterial culture was followed from the previous report 16 . To obtain planktonic bacteria, we started 100 ml cultures from OD 0.003 in 7H9/ADC (without Tween 80) and incubated aerobically in static conditions at 37 °C for 1 week.…”
Section: Transposon Mutagenesis and Preparation Of Bacterial Samples mentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial biofilm formation can be influenced by diverse microenvironmental conditions ( Van Wamel et al, 2007 ; Alves et al, 2010 ; Wang et al, 2015 ; Totani et al, 2017 ). Tobaco smoke, a contributor to various infectious diseases, has been shown to enhance bacterial biofilm formation in multiple species, such as Staphylococcus aureus, Streptococcus pneumoniae , and Streptococcus mutans ( Hutcherson et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these technologies have great potential for observing and quantifying the microenvironmental conditions that shape the survival strategies of bacteria, such as biofilms. Biofilms are strictly regulated by their surrounding microenvironments [ 14 , 15 , 16 ]; these might be able to be tightly controlled using microfluidic devices. Moreover, microfluidic cell culture systems have provided great potential for culturing currently viable but non-culturable bacteria (VBNCs) in laboratories, while discovering the mechanisms behind their phenotype [ 11 ].…”
Section: Introductionmentioning
confidence: 99%